Towards a Nomadic Ethics in Translation Praxis. Issue 2 (2nd July 2016) - van Heerden, Chantelle Gray
Abstract : In this article I examine how translation practitioners might begin to develop a praxis that is informed by a nomadic ethics which is not reliant on a normative or regularizing ethics/morality, but rather constitutes an orientation founded on heterogeneity and the repudiation of universality. In order for such a praxis to be effectuated, I argue that translations have to take into consideration the historicity of master narratives so that meaning becomes disentangled from the semantics and grounded in a materialist philosophy. Because translation does not occur in a vacuum; it is influenced by myriad material flows, some apparent and some not which, in turn, are linked to certain forms of knowledge and power. To support my argument, I refer to the philosophy of Gilles Deleuze and Félix Guattari, and apply it to the use of a number of stylistic and linguistic devices in the oeuvre of Ingrid Winterbach.